AN ANALYSIS OF SEVENTH GRADE STUDENTS ABILITY IN WRITING PROCEDURE TEXT AT SMPN 2 KOTA SERANG: Analisis Kemampuan Menulis Teks Prosedur Siswa Kelas Tujuh di SMPN 2 Kota Serang - Deprilya, Aisyah; Aira Juniar Mutiara Halim; Ika Handayani; Diyah Setyorini; Mentari Viona (Aisyah Journal of English Language Teaching (AIJELT), 2025)
This study examines the ability of seventh-grade students at SMPN 2 Kota Serang to write procedure texts. Using a quantitative descriptive method, data were collected from a sample of 35 students through a written test where students created their own procedure texts. The findings revealed that 51.43% of students achieved "very good" scores (90 and above), 14.29% fell into the "good" category (70–85), and 34.29% scored in the "sufficient" range (50–65). No students were classified as "failed." The average score was 79.4, indicating a general proficiency in writing procedure texts. However, the analysis identified recurring linguistic errors, including inconsistent verb tense usage, incorrect article placement, and fragmented sentence structures. Students also demonstrated challenges in spelling, vocabulary selection, and providing clear, detailed instructions. These issues affected the overall coherence and readability of their texts. The study concludes that while students show foundational skills in writing procedure texts, targeted instruction on grammar, cohesion, and descriptive detail is essential to enhance their writing proficiency.